Management of Religious and Cultural Development at Darul Ulum Vocational School Donorojo Jepara - Haryanto Haryanto (Journal of Innovative and Creativity, 2025)
This study aims to describe the management of religious culture development at Darul Ulum Donorojo Jepara Integrated Vocational School. This research was conducted using a descriptive method with a qualitative approach. Data collection techniques included observation, interviews, and documentation. The research subjects were the foundation administrators, committee, principal, vice principal, teachers, parents, and students. The results of field research concluded that the management of religious cultural development at includes (1) planning, which is designed in a teacher meeting and implemented based on the principal's policy, (2) organizing, by dividing work into smaller tasks to people according to their abilities, (3) actuating, by the instilling of religious culture is carried out through several religious habits in schools such as greetings when meeting, shaking hands when meeting, or saying hello, reading the Koran in the first hour, congregational Dzuhur prayer, and regulations on wearing sarongs for male students, (4) evaluating, is executed by compiling the SKK (Religious Competency Standards) which contain religious activities that students must carry out. Evaluation of moral values is monitored using a student control book. Supporting factors for implementing school culture management include vision, mission, relationships, curriculum, learning, and leadership. In addition to the customs that constitute culture, several structured organizations support the development of religious culture in schools. Inhibiting factors include time and maintenance management. Jn conclusion the management of religious and cultural development has been implemented well and systematically. Students, teachers, and staff participate in religious and cultural practices at the school.